2021
DOI: 10.1107/s205252062100398x
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure and environment effects in selenourea and its labile crystal field around molecules

Abstract: Ambient-pressure trigonal phase α of selenourea SeC(NH2)2 is noncentrosymmetric, with high Z′ = 9. Under high pressure it undergoes several intriguing transformations, depending on the pressure-transmitting medium and the compression or recrystallization process. In glycerine or oil, α-SeC(NH2)2 transforms into phase β at 0.21 GPa; however in water, phase α initially increases its volume and can be compressed to 0.30 GPa due to the formation of α-SeC(NH2)2·xH2O. The single crystals of α-SeC(NH2)2 and of its pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Two crystal structures determined at 100 K (Luo & Dauter, 2017) and 173 K (Rutherford & Calvo, 1969) are both consistent with phase (i.e. space group P3 1 , Z 0 = 9) (Roszak & Katrusiak, 2021;Rutherford & Calvo, 1969). Our differential scanning calorimetry (DSC) measurements revealed a first-order phase transition at 381.0 K and a new solid selenourea phase stable below the melting point at 473 K (Fig.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Two crystal structures determined at 100 K (Luo & Dauter, 2017) and 173 K (Rutherford & Calvo, 1969) are both consistent with phase (i.e. space group P3 1 , Z 0 = 9) (Roszak & Katrusiak, 2021;Rutherford & Calvo, 1969). Our differential scanning calorimetry (DSC) measurements revealed a first-order phase transition at 381.0 K and a new solid selenourea phase stable below the melting point at 473 K (Fig.…”
Section: Introductionsupporting
confidence: 68%
“…The 100 K/0.1 MPa points were determined by Luo & Dauter (2017). The molecular volume of phase (the open circle) is also indicated for its lowest limit of pressure range at 0.21 GPa (Roszak & Katrusiak, 2021). Where not indicated, the estimated standard deviations are smaller than the plotted symbols.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the recrystallizations of the pure molten dlmenthol yielded polymorph below 0.40 GPa and polymorph above 0.40 GPa. Because no other compounds except dl- menthol were present in the DAC chamber, this series of experiments showed that no solvent effects, such as stochastic sorption, take place (Roszak & Katrusiak, 2021;Olejniczak et al, 2022a).…”
Section: Resultsmentioning
confidence: 85%